Shame Regulation Therapy for Families A Systemic Mirroring Approach - Weinblatt, Uri (Springer International Publishing, 2018)
This accessible guide introduces systemic mirroring, an innovative approach to understanding and managing the disruptive presence of shame in family therapy. Shame is analyzed in individual and interpersonal contexts, and in two basic problematic states-experiencing too much or too little shame-often found at the root of serious problems between children and their parents. The author offers potent conversation-based strategies for working with children, adolescents, and their families, and for working with parents to resolve their own shame issues so they can improve their relationships with their children. The author also illustrates how shame regulation can improve the bond between client and therapist and produce lasting effects as clients learn to disengage from shame. This practical resource: Offers an innovative approach to dealing with shame in therapy Integrates practical methods for use with children, adolescents, and parents Discusses how shame derails interpersonal communication Provides interventions for shame management and dealing with the state of shamelessness Shows how parents can regulate their own shame at the couple level Applies these methods to school settings Shame Regulation Therapy for Families aides the work of professionals such as psychologists, psychiatrists, social workers, and school psychologists who work with children and their families on shame management. .